2020
DOI: 10.1007/s42154-020-00119-9
|View full text |Cite
|
Sign up to set email alerts
|

Micro Gas Turbine Range Extender Performance Analysis Using Varying Intake Temperature

Abstract: This document is the author's post-print version, incorporating any revisions agreed during the peer-review process. Some differences between the published version and this version may remain and you are advised to consult the published version if you wish to cite from it.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…The analysis indicated that the temperatures of the tray predicted by the simulation are consistent with the experimental results. Thus, the feasibility of the thermal model for thermal analyses and the design of full‐scale battery systems was confirmed 36 …”
Section: Heat Generation Mechanisms and Thermal Models Of Libsmentioning
confidence: 81%
See 2 more Smart Citations
“…The analysis indicated that the temperatures of the tray predicted by the simulation are consistent with the experimental results. Thus, the feasibility of the thermal model for thermal analyses and the design of full‐scale battery systems was confirmed 36 …”
Section: Heat Generation Mechanisms and Thermal Models Of Libsmentioning
confidence: 81%
“…Therefore, it is crucial to grasp the internal heat generation mechanism of LiBs. 35,36 Under normal working conditions, the internal heat generation of LiBs is usually inevitable due to electrochemical reactions during charge and discharge cycles, and is also affected by environmental conditions; in the case of thermal runaway, the heat generation of LiBs comes from the undesired side reactions at high temperatures. The categories of heat generation and dissipation within the battery system are depicted in Figure 2.…”
Section: Heat Generation Mechanismmentioning
confidence: 99%
See 1 more Smart Citation
“…Atomic O/C ratio 0.0049 Within the exhaust system, the gaseous emissions without the after-treatment process were measured using a gas analyzer, which was connected to a pitot tube flow meter (PTFM). The calibration of the PTFM was based on work performed by Shah et al [27]. Using the same parameters setting and test definitions, the experimental validation recurred two times.…”
Section: Experimental Validation Of the Four Power Demand Strategiesmentioning
confidence: 99%
“…Some countries plan to completely phase out the fossil fuel-based two-wheeled vehicle from 2025 such as India 6) , which has the biggest market for such vehicles. These policies are accelerating the E-TWV development in terms of the range anxiety associated with the battery energy density 7) , the cost premium that customer willing to invest for the product value 8) and the charging infrastructure readiness to meet the high demand and fast charging requirement 9) . The majority of E-TWV developers focuses on the effort to reduce the range anxiety issue and to minimize the cost premium for increasing the product demand 10) .…”
Section: Introductionmentioning
confidence: 99%